Agomelatine facilitates positive versus negative affective processing in healthy volunteer models. - Harmer CJ; de Bodinat C; Dawson GR; Dourish CT; Waldenmaier L; Adams S; Cowen PJ; Goodwin GM; Harmer, Catherine J; de Bodinat, Christian; Dawson, Gerard R; Dourish, Colin T; et al. (Journal of Psychopharmacology, 2011)
Agomelatine is a new antidepressant with a novel profile of pharmacological action. The clinical efficacy of agomelatine has been established in major depression, but its actions on emotional bias are unknown. Consequently, the current experimental study assessed the effect of agomelatine on emotional processing in healthy volunteers using an Emotional Test Battery shown to be sensitive to serotonin and noradrenaline reuptake inhibitors. Volunteers were randomized to receive placebo, 25 mg or 50 mg of agomelatine over a 7-day period in a double-blind parallel groups design. Emotional processing (n = 48) was assessed on the morning of day 8 using the Emotional Test Battery which included facial expression recognition, emotional memory, attentional visual probe and emotion-potentiated startle. Mood and subjective state were monitored before and during treatment. Agomelatine (25 mg) decreased subjective ratings of sadness, reduced recognition of sad facial expressions, improved positive affective memory and reduced the emotion-potentiated startle response. The results show that agomelatine has more selective effects on the processing of social facial cues than conventional antidepressants, which could contribute to less blunting of emotional experience. The study highlights the potential value of volunteer models in drug development for screening and profiling of novel antidepressants.